Strength and Ductility Evaluation of L-Shape Shear Connectors in Composite Floors - G. P. Tonkih; D. A. Chesnokov (Железобетонные конструкции)
Existing composite floor design approaches require technical data on strength and ductility of shear connectors, which can be defined only by shear tests. The article discusses the failure modes of composite floor shear connection, made of powder-actuated shear connectors. The influence assessment of the main detailing parameters on the strength and deformability of shear connectors was executed.  The database for analysis included the results of shear tests performed by both the authors and other researchers. According to the results of the study, the dependence of the strength and deformability of shear connectors on their height, orientation relative to the shear force vector, the strength of the concrete slab and the geometric parameters of the profiled flooring was estimated.